Analysis of developed transition road safety barrier systems - Soltani, M.; Moghaddam, T.B.; Karim, M.R.; Sulong, N.H. (2013)
Road safety barriers protect vehicles from roadside hazards by redirecting errant vehicles in a safe manner as well as providing high levels of safety during and after impact. This paper focused on transition safety barrier systems which were located at the point of attachment between a bridge and roadside barriers. The aim of this study was to provide an overview of the behavior of transition systems located at upstream bridge rail with different designs and performance levels. Design factors such as occupant risk and vehicle trajectory for different systems were collected and compared. To achieve this aim a comprehensive database was developed using previous studies. The comparison showed that Test 3-21, which is conducted by impacting a pickup truck with speed of 100 km/h and angle of 25 to transition system, was the most severe test. Occupant impact velocity and ridedown acceleration for heavy vehicles were lower than the amounts for passenger cars and pickup trucks, and in most cases higher occupant lateral impact ridedown acceleration was observed on vehicles subjected to higher levels of damage. The best transition system was selected to give optimum performance which reduced occupant risk factors using the similar crashes in accordance with Test 3-21. Â© 2013 Elsevier Ltd. All rights reserved.